A Critical Approach to Evaluating Clinical Efficacy, Adverse Events and Drug Interactions of Herbal Remedies - Izzo, Angelo A.; Hoon-Kim, Sung; Radhakrishnan, Rajan; Williamson, Elizabeth M. (Phytotherapy research, 2016)
Systematic reviews and meta‐analyses represent the uppermost ladders in the hierarchy of evidence. Systematic reviews/meta‐analyses suggest preliminary or satisfactory clinical evidence for agnus castus (Vitex agnus castus) for premenstrual complaints, flaxseed (Linum usitatissimum) for hypertension, feverfew (Tanacetum partenium) for migraine prevention, ginger (Zingiber officinalis) for pregnancy‐induced nausea, ginseng (Panax ginseng) for improving fasting glucose levels as well as phytoestrogens and St John's wort (Hypericum perforatum) for the relief of some symptoms in menopause. However, firm conclusions of efficacy cannot be generally drawn. On the other hand, inconclusive evidence of efficacy or contradictory results have been reported for Aloe vera in the treatment of psoriasis, cranberry (Vaccinium macrocarpon) in cystitis prevention, ginkgo (Ginkgo biloba) for tinnitus and intermittent claudication, echinacea (Echinacea spp.) for the prevention of common cold and pomegranate (Punica granatum) for the prevention/treatment of cardiovascular diseases. A critical evaluation of the clinical data regarding the adverse effects has shown that herbal remedies are generally better tolerated than synthetic medications. Nevertheless, potentially serious adverse events, including herb–drug interactions, have been described. This suggests the need to be vigilant when using herbal remedies, particularly in specific conditions, such as during pregnancy and in the paediatric population. Copyright © 2016 John Wiley & Sons, Ltd.